Lessons learnt from multiple private land conservation programs in Canada to inform species at risk conservation. (14th May 2022) - Reiter, Dana; Pittman, Jeremy; Ayambire, Raphael Anammasiya; Brown, H. Carolyn P.; Colla, Sheila R.; Loewen, Theresa M.; McCune, Jenny L.; Olive, Andrea; Parrott, Lael
Abstract : Action at local scales is needed to reduce documented declines in global biodiversity. Agricultural land constitutes 6.8% of the surface area of Canada, including more than 20 million hectares of grazing pasture alone, providing habitat to many species at risk of extinction. In Canada, where a voluntary stewardship approach is the main strategy for species at risk conservation on privately owned and managed lands, the challenge is to create conservation programs that maximize participation. We reviewed research on voluntary conservation programs on agricultural lands from five Canadian provinces to understand which approaches were most effective in maximizing participation. The objective of this paper is to contribute to policy development for conservation on private lands in Canada. We highlight common themes from all five regions. Key findings include the value of establishing a local delivery agent for the program, and the importance of designing the program to be in alignment with existing agricultural operations. Private landowners may build trust with local program managers, and are more open to making subtle adjustments to their land management rather than major changes. We conclude with eight recommendations to support the development of high impact species at risk stewardship programs on agricultural lands in Canada. Key Messages: The use of a local program delivery agency that engages in meaningful, long‐term stakeholder engagement and collaboration builds trust and encourages participation. Land managers appreciate flexible and collaborative program design that aligns with current agricultural land management. Stable, long‐term organizational funding and strong financial incentives for land managers are key. Les leçons des programmes de conservation des espèces en péril sur les terres privées à vocation agricole au Canada: La nécessité de mettre en place des mesures aux échelles locale et régionale pour réduire le déclin de la biodiversité mondiale est largement reconnue. Les terres agricoles représentent 6, 8% de la superficie du Canada, y compris des millions d'hectares en pâturages où l'on retrouve de nombreuses espèces menacées. Dans ce pays, le défi sur le plan de la conservation consiste donc à créer des programmes de partenariat de gestion qui maximisent la participation des grands propriétaires fonciers privés en milieu agricole. L'objectif de la présente recherche est de contribuer à l'élaboration de politiques publiques dans ce domaine. À cette fin, nous avons recensé et anlaysé les recherches relatives aux programmes de conservation sur des terres agricoles en tenure privée dans cinq provinces canadiennes dans le but de mieux connaître les mesures de partenariat. Nous mettons ici en évidence les éléments communs des programmes dans ces cinq territoires. Nos conclusions traitent de l'importance de la mise en place d'un agent local de promotion du programme et de la conception d'une approche qui s'harmonise avec les opérations agricoles existantes. En effet, les propriétaires de terres privées doivent établir un lien de confiance avec les gestionnaires de programmes. Ils sont alors plus ouverts à apporter des ajustements aux modes de gestion de leurs terres. Pour finir, nos résultats comportent également huit recommandations qui viennent appuyer le développement de programmes de gestion des espèces en péril sur les terres privées à vocation agricole .